Yield Performance and Adoption of Released Sorghum Varieties in Ethiopia - Kinfe, Hailegebrial; Tesfaye, Adane (Edelweiss Applied Science and Technology, 2018)
Sorghum national average productivity in Ethiopia is 2.1 tons/ha which is far below the global average of 3.2 tons/ha due to the problem of drought, striga, insect pest (stalk borer, midge, and shoot fly),diseases (anthracnose and smut), soil fertility decline, inadequate adoption of existing improved varieties, lack of high yielding and good quality sorghum varieties. The Ethiopian government is pursuing a strategy of improving Sorghum productivity primarily through agricultural intensification, involving an increased use of inputs, including seeds of improved crop varieties and involved sorghum plant breeding since 1976 with different objectives and released many improved sorghum varities. However the yield performance, adoption intensity and adoption rate of the released sorghum varieties at regional and national level were not well studied. So this research intiated with the following objectives: To summarize the trend of sorghum production and productivity in Ethiopia. To asses performance of improved sorghum varieties yield and their level of adoption. To evaluate factors that determines adoption of improved sorghum in Ethiopia. The assessment was also done using secondary data from different sources. So, as a conclusion to increase the adoption rate and intensity of the released sorghum varieties across their suitable agro ecology and based on the objective of the target improved sorghum varities at the time of variety registration, agricultural extension should be strength and linkage between the department of integrated crop improvement with socio economics and agricultural extension should be improved. With this at variety development farmers better to participate and include their selection criteria, interest, problem and increase adoption of the improved sorghum varieties. Socio economic, demographic and institutional factors also played negative impact on slow adoption of the improved sorghum varieties.